2012
DOI: 10.4097/kjae.2012.63.6.555
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and remifentanil in the perioperative management of an adolescent undergoing resection of pheochromocytoma -A case report-

Abstract: A 15-year-old adolescent with unilateral multiple adrenal pheochromocytoma had an episode of subcortical intracerebral hemorrhage and seizure 6 weeks before the surgery. He was pretreated with terazosin, losartan, atenolol and levetiracetam for 2 weeks. Dexmedetomidine was started in the preoperative waiting area, and a combination of dexmedetomidine and remifentanil was continuously infused for most of anesthetic time. To control blood pressure, bolus injection of remifentanil and low-dose infusion of sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…31,36 Studies have indicated that continuous infusion of remifentanil and dexmedetomidine could maintain hemodynamic stability, including heart rate and blood pressure. [37][38][39] Additionally, this combination strategy 18 [8,33] 0.218 − 16 [8,30] 18 [8,33] 0.211 − 16 [8,28] 18 [9,33] 0…”
Section: Critical Care Medicine Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,36 Studies have indicated that continuous infusion of remifentanil and dexmedetomidine could maintain hemodynamic stability, including heart rate and blood pressure. [37][38][39] Additionally, this combination strategy 18 [8,33] 0.218 − 16 [8,30] 18 [8,33] 0.211 − 16 [8,28] 18 [9,33] 0…”
Section: Critical Care Medicine Discussionmentioning
confidence: 99%
“…31,36 Studies have indicated that continuous infusion of remifentanil and dexmedetomidine could maintain hemodynamic stability, including heart rate and blood pressure. 37–39 Additionally, this combination strategy reduces the dose dependence of calcium channel blockers like nimodipine by attenuating the sympathetic response. 40 This establishes a scientific foundation for the integrated approach and elucidates why this strategy could contribute to early intensive blood pressure–lowering.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The use of dexmedetomidine and remifentanil for an adolescent undergoing resection of phaeochromocytoma has been successfully reported by Jung et al . [ 5 ] Dexmedetomidine and sevoflurane were successfully used by Khetarpal et al . in an adult undergoing resection of phaeochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Its sympatholytic properties ( Gertler et al ., 2001 ) render this agent attractive for the anesthetic management of phaeochromocytoma resection. While its use as an intraoperative constant rate infusion (CRI) has been described in humans ( Wong and Cheung, 2004 ; Bryskin and Weldon, 2010 ; Schumann and Hudcova, 2010 ; Jung et al ., 2012 ; Khetarpal et al ., 2014 ; Ali Erdogan et al ., 2015 ; Dias et al ., 2015 ; Hedge et al ., 2016 ; Shrestha et al ., 2016 ; Giordano et al ., 2019 ; ), concomitant vasodilators were still frequently needed during surgical manipulation. There is, to date, a single case report of its perioperative use for phaeochromocytoma removal in a canine patient ( Viilmann and Vettorato, 2021 ).…”
Section: Introductionmentioning
confidence: 99%